Variability, heritability and genetic advance in landraces of culinary melon (Cucumis melo L.) - Rakhi, R.; Rajamony, L. (Journal of Tropical Agriculture, 2006)
Forty two landraces of culinary melons (Cucumis melo L.) were evaluated for variability, heritability and genetic advance. Genotypic coefficient of variation and phenotypic coefficient of variation were highest for yield per plant followed by fruit weight, fruit per plant, keeping quality of fruits and 1000-seed weight. High heritability coupled with high genetic advance was noted for fruit length, 1000-seed weight, average fruit weight and keeping quality of fruit indicating the scope for improvement of culinary melon through selection